Ultrasonography Measurement of Abdominal Subcutaneous Fat Thickness and Its Correlation with Hyperlipidemia and Steatohepatitis in Obese People - Pathak, Dr. Roshani; Pradhan, Sunil; Tuladhar, Abhushan; Shrestha, Amit; Acharya, Riwaz (International Journal of Innovative Research in Medical Science, 2018)
Introduction Unhealthy dietary practices, sedentary lifestyle and obesity have emerged as major risk factors of Non communicable diseases (NCD).[1] In India there is shift in dietary patterns to more ‘Western’ diets rich in saturated fat, refined foods and sugar and low in fibre[2] due to which there is a higher prevalence of traditional cardiovascular disease risk factors such as obesity, physical inactivity, tobacco use and high intake of saturated fat.[3] In 2000, the International Obesity Task Force of the WHO (IOTF-WHO) proposed a modification of National Heart, Lung, and Blood Institute guidelines on overweight/obesity which is as follows : Overweight, 23 to <25; class I obesity, 25 to <30; and class II obesity, ≥30. Redefining the obesity cut-off (BMI >25) creates an “obesity burden” in urban India.[4]